The Intervention Areas of the Psychologist in Pediatric Palliative Care: A Retrospective Analysis - Santini, Anna; Avagnina, Irene; Marinetto, Anna; De Tommasi, Valentina; Lazzarin, Pierina; Perilongo, Giorgio; Benini, Franca (Frontiers in Psychology, 2022)
Infants, children and adolescents with life-limiting and life-threatening disease need long-term care that may change according to disease’s natural history. With the primary goal of quality of life, the psychologist of PPC network deals with a large variety of issues. Little consideration has been given to the variety of intervention areas of psychology in PPC that concern the whole life span of the patient and family. The PPC network is composed by a multidisciplinary team of palliative care specialists that intervenes at home, in the hospital and in every place where the patient is living. The network coordinates different public health services to respond to clinical, psychosocial and spiritual needs. In these scenarios, the psychological need is not a single event but a moment inserted in the complexity of the child's needs. This retrospective monocentric project consists of an analysis of characteristics of psychological interventions in our PPC service. The time frame taken into consideration is 2019-2020, analysing the clinical records of 186 patients of Paediatric Palliative Care and Pain Service of Veneto Region (Italy). The areas that emerged in the analysis show how the intervention of the psychologist in PPC does not concern only end-of-life, but a series of topics that are significant for the family to guarantee psycho-social wellbeing oriented towards the best quality of life. In conclusion, these different topics highlight the complexity of the child and family experience. This variety must be taken into consideration, psychologist must increase holistic support with a dedicated skills curriculum.